The Advantages of Pleco and Google Translate Applications in Assisting Mandarin Language Learning. Issue 1 (February 2021) - Ying, Yi; Theresia,; Febriana, Vivi
Abstract: As technology develops, dictionaries have changed from paper to electronic. Electronic dictionaries can be an alternative medium for language learning because they combine sound, visuals and text that make learning foreign languages easier. One example of using an electronic dictionary is in reading subjects. Users can learn about how to pronounce a vocabulary and sound tones correctly by utilizing the audio feature in an electronic dictionary. Vocabulary recall through mobile device applications is far more effective than through other media. The electronic dictionary application that is widely used by Chinese Literature students in learning Mandarin is the Pleco and Google Translate application. Therefore, the authors are interested in making comparisons of the similarities and differences between the two applications for the recommendation of Mandarin learning aids. This study uses a comparison method by comparing the functions of the two e-dictionaries. From the results of the comparison, both applications have keyboard features, handwriting features, voice record features and scanning features for translating words. The difference is in the radical features, stroke, number words and sentences sample